2013
DOI: 10.1007/s10792-013-9795-6
|View full text |Cite
|
Sign up to set email alerts
|

Diet and cataract: a case–control study

Abstract: We conducted a case-control study to assess the association between diet and risk of cataract in Athens, Greece. Totals of 314 cases and 314 frequency-matched controls of both sexes, aged 45-85 years and attending the ophthalmology department of a major teaching hospital in Athens, Greece, were included in the study. All participants were interviewed using a semi-quantitative food-frequency questionnaire, covering the average frequency of consumption of about 120 food items. Analyses were conducted through mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
48
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(54 citation statements)
references
References 39 publications
6
48
0
Order By: Relevance
“…Dietary vitamin E intake and risk of age-related cataract The association between dietary vitamin E intake and ARC risk was examined in eight articles (15)(16)(17)43,45,50,53,56) with eight studies including 15 021 participants and 2258 cases. The highest v. the lowest dietary vitamin E intake was statistically significantly associated with the risk of ARC (RR = 0·73; 95 % CI 0·58, 0·92; I 2 = 69·1 %; P heterogeneity = 0·002; Fig.…”
Section: Quantitative Synthesismentioning
confidence: 99%
“…Dietary vitamin E intake and risk of age-related cataract The association between dietary vitamin E intake and ARC risk was examined in eight articles (15)(16)(17)43,45,50,53,56) with eight studies including 15 021 participants and 2258 cases. The highest v. the lowest dietary vitamin E intake was statistically significantly associated with the risk of ARC (RR = 0·73; 95 % CI 0·58, 0·92; I 2 = 69·1 %; P heterogeneity = 0·002; Fig.…”
Section: Quantitative Synthesismentioning
confidence: 99%
“…Age, ultraviolet light exposure, smoking, and corticosteroid use are recognized risk factors associated with cataract formation [7,8]. Besides other risk factors such as abdominal obesity [9] and hormonal therapy [10], the production of proinflammatory components increases the levels of free oxygen radicals [11,12], which have been associated with an increasing risk of cataract.…”
Section: Introductionmentioning
confidence: 99%
“…Although diets rich in antioxidants have been identified in several studies to reduce the incidence of oxidative stress-related eye diseases, various antioxidant supplement studies provided conflicting findings [6,7,8,9]. In contrast, the intake of other food groups such as meat and related micronutrients such as cholesterol has been identified in various studies to increase the risk of oxidative stress-related eye conditions [10,11,12,13]. The impact of dietary antioxidant intake on the risk of oxidative stress-related eye diseases has been examined previously [13], but typically the studies addressed the effect of antioxidant supplements or fruit and vegetables in isolation, rather than the total dietary intake [14].…”
Section: Introductionmentioning
confidence: 99%
“…With regards to CAT, the evaluation of the literature indicates a higher dietary consumption of fruit and vegetables and vitamin C (including supplementation) appears to be associated with the most consistent risk reduction [13,14]. Vitamin E dietary intake and supplementation was also consistent with risk reduction in the majority of studies; however, findings on vitamin E supplementation suggested no observed differences in the rate of cataract extraction and lens characteristics between groups [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation